Longitudinal associations between exclusive, dual and polytobacco use and respiratory illness among youth - Luis Zavala-Arciniega; Steven Cook; Jana L. Hirschtick; Yanmei Xie; Richa Mukerjee; Douglas Arenberg; Geoffrey D. Barnes; David T. Levy; Rafael Meza; Nancy L. Fleischer (BMC, 2024)
Abstract Background The health consequences of polytobacco use are not well understood. We evaluated prospective associations between exclusive, dual, and polytobacco use and diagnosed bronchitis, pneumonia, or chronic cough among US youth. Methods Data came from Waves 1-5 of the Population Assessment of Tobacco and Health Study. We categorized time-varying past 30-day tobacco use into seven categories: (1) non-current use; exclusive use of 2) cigarettes, 3) e-cigarettes, and 4) other combustible products (OC; pipes, hookah, and cigars); dual use of 5) e-cigarettes + cigarettes or e-cigarettes + OC, and 6) cigarettes + OC; and 7) polyuse of all three products. The outcome was parent-reported diagnosis of bronchitis, pneumonia, or chronic cough among youth. We conducted weighted multilevel Poisson models (person n = 17,517, 43,290 observations) to examine the longitudinal exposure-outcome relationship, adjusting for covariates: sex, age, race and ethnicity, parental education, body mass index, secondhand smoke exposure, and household use of combustible products. Results Compared to nonuse, exclusive cigarette use (Risk Ratio (RR) = 1.83, 95% CI 1.25-2.68), exclusive e-cigarette use (RR = 1.53, 95% CI 1.08-2.15), combustible product + e-cigarette dual use (RR = 1.90, 95% CI 1.18-3.04), cigarettes + OC dual use (RR = 1.96, 95% CI 1.11-3.48), and polytobacco use (RR = 3.06 95% CI 1.67-5.63) were associated with a higher risk of bronchitis, pneumonia, or chronic cough. In additional analyses, we found that the risk ratio for polytobacco use was higher compared to exclusive e-cigarette use (RR 2.01 CI 95% 1.02-3.95), but not higher compared to exclusive cigarette use (RR 1.67 CI 95% 0.85-3.28). Conclusion We found that exclusive, dual, and poly tobacco use were all associated with higher risk of bronchitis, pneumonia, or chronic cough compared to non-current use.